Preparation of a Novel Perilla Essential Oil/Grape Seed Extract–Chitosan/Gelatin Composite Edible Gel Film and Its Application in the Preservation of Grass Carp - Shan Xue; Rui Xu; Jia Liu (Gels)
In this study, a new edible gel of Perilla essential oil (PE)/grape seed extract (GSE)–chitosan/gelatin was prepared, and it was applied to the preservation of silver carp. By establishing a fuzzy mathematical model, using a single-factor experiment and Box–Behnken response surface optimization combined with matlab analysis, the optimum preparation conditions of composite gel films were determined: the addition of PE (p < 0.01) was 6.91 μL/mL, the addition of GSE (p < 0.05) was 0.45 mg/mL, and the addition of gelatin (p > 0.05) was 1.63%. Under these conditions, the composite gel films exhibited an excellent water vapor barrier and mechanical properties. Using Fourier-transform infrared spectroscopy (FTIR) analysis, it was found that the addition of PE enhanced or weakened the absorption peaks, indicating the molecular interaction between PE and the substrate. Scanning electron microscopy (SEM) observed that the surfaces of the composite gel films with added PE were smooth, but there were a few pores in the cross-section. X-ray diffraction (XRD) analysis showed that PE had good compatibility with other components. The fresh-keeping experiment showed that the composite gel films could significantly prolong the fresh-keeping period of grass carp. After 10 days of storage at 4 °C, compared with the blank group (without plastic wrap) and the control group (with composite gel film, no PE added), the experimental group (with composite gel films, PE added) showed better fresh-keeping effect in terms of sensory score, moisture content, pH value, TBARS value, and TVB-N value (p < 0.05). Correlation analysis further confirmed the positive effects of composite gel films on water content, pH value, TVB-N, and other quality indexes of silver carp, indicating that the composite gel films will have broad application prospects in the food preservation field. This study provides an innovative basis and theoretical basis for the development and application of natural polysaccharide/protein composite edible film, which is helpful to promote the development of green food-packaging materials.